Assessing the Comparative Efficacy and Safety of Warfarin and Rivaroxaban for Cancer Associated Thrombosis: Experience From a Resource Limited Setting - Abel Tenaw Tasamma; Tsegab Alemayehu Bukate; Abdulrahim Mehadi; Bereket Tagesse Handiso; Beniam Yohannes Kassa; Eman Omer Hassen; Zekarias Seifu Ayalew; Dawit Habtie Tegegne; Gebeyehu Tessema Azibte; Tigest Abebaw Zewdie; Tinsaye Zergaw Shihur; Yonas Degelo Geremamo; et al. (Cancer Reports)
ABSTRACT Background Thromboembolic events are a common cause of morbidity and mortality in patients with cancer. While direct‐acting oral anticoagulants (DOACs) have been established as the preferred agents of anticoagulation in most patients with cancer, data in resource‐limited settings is limited. Aims The study aims to assess the comparative efficacy and safety of warfarin and rivaroxaban for cancer‐associated thrombosis (CAT) in a resource‐limited setting. Methods and results A single‐center retrospective cohort study was conducted on 201 patients who were on follow‐up from September 2021 to August 2023. The patients were categorized into two groups (1) warfarin and (2) rivaroxaban. They were then retrospectively followed for 12 months. The primary endpoint was a composite of recurrence of venous thromboembolism (VTE), major bleeding event, or all‐cause mortality. The Cox regression model was used to compare the outcome of the two groups. The baseline mean (standard deviation) age of the patients was 48.4 (15.0) and 140 (69.7%) of them were female. 41.3% of the participants had one or more comorbidities, and the most common types of cancer were gynecologic (28.9%), hematologic (21.4%), and intra‐abdominal (16.9%). The most common type of thrombosis was deep vein thrombosis (DVT) (77.1%). The primary composite outcome of VTE recurrence, major bleeding event, and all‐cause mortality occurred in 25 (24.3%) patients in the warfarin group and 11 (11.2%) in the rivaroxaban group (hazard ratio (HR), 0.48; 95% confidence interval (CI), 0.24–0.97; p = 0.041). Conclusion Rivaroxaban was found to be more efficacious and safer than warfarin for patients with CAT in a resource‐limited setting. This finding is congruent with reports from resource‐abundant countries and recommendations from major international societies.